Controlling Fusarium oxysporum tomato fruit rot under tropical condition using both chitosan and vanillin - Safari, Zahir Shah; Ding, Phebe; Jaafar, Juju Nakasha; Yusoff, Siti Fairuz (Multidisciplinary Digital Publishing Institute, 2021)
Tomato Lycopersicon esculentum Mill. is one of the most cultivated and widely consumed vegetables in the world. However, it is very susceptible to the infection initiated by Fusariumoxysporum fruit rot, which shortens post-harvest life and thus reduces market value. This disease can be regulated appropriately by the application of synthetic fungicides. However, chemical fungicides constitute a serious health risk, and have harmful environment effects and increase disease resistance, even when microbes are dead. Hence, to overcome this problem, chitosan and vanillin, which have antimicrobial bioactive properties against the growth of microorganisms, could be an alternative to disease control, while maintaining fruit quality and prolonging shelf life. The aim of this research was to evaluate the antimicrobial activity of chitosan and vanillin towards the inoculate pathogen and to investigate the effect of chitosan and vanillin coating in vivo on Fusarium oxysporum fruit rot and defense-related enzymes (PAL, PPO and POD). Chitosan and vanillin in aqueous solutions, i.e., 0.5% chitosan + 10 mM vanillin, 1% chitosan + 10 mM vanillin, 1.5% chitosan + 10 mM vanillin, 0.5% chitosan + 15 mM vanillin, 1% chitosan + 15 mM vanillin and 1.5% chitosan + 15 mM vanillin, were used as edible coatings on tomatoes stored at 26 ± 2 °C and 60 ± 5 relative humidity. The result revealed 1.5% chitosan + 15 mM vanillin was able to control disease incidence by 70.84% and severity by 70%. These combinations of coatings were also able to retain phenylalanine ammonia-lyase (PAL), peroxidase activity (POD), and polyphenol oxidase (PPO) enzyme activities as well as prolong shelf life of tomatoes up to 15 days.